The Influence of Perceived Family Support and Perceived Workplace Support on Work Life Balance and Employee Performance (Study at the Makassar City Employment Service) - Sri Hamdana Syahrul; Ahmad Ac; Samsul Rizal (Pustaka Digital Indonesia, 2026)
The purpose of this study is to analyze the influence of Perceived Family Support and Perceived Workplace Support on Work Life Balance and Employee Performance at the Makassar City Manpower Office. This sample was taken from employees of the Makassar City Manpower Office. The type of data used in this study is quantitative data obtained from distributed questionnaires and related to the problem being studied. Data collection was carried out using research instruments, data analysis was quantitative/statistical, with the aim of testing the established hypothesis. Based on the results of the study using statistical calculations through the Statistical Package for the Social Science (SPSS) application, it can be concluded that: Analysis of the influence of Perceived Family Support on Employee Performance obtained a significance value of 0.411> 0.05. So it can be concluded that directly does not have a positive influence Perceived Family Support on Employee Performance, Analysis of the influence of Perceived Workplace Support on Employee Performance. Obtained a significance value of 0.000 <0.05. So it can be concluded that there is a direct significant influence of Perceived Workplace Support on Employee Performance, Analysis of the influence of Perceived Family Support on Work Life Balance. A significance value of 0.000 <0.05 is obtained. So it can be concluded that there is a direct significant influence of Perceived Family Support on Work Life Balance, Analysis of the influence of Perceived Workplace Support (X2) on Work Life Balance. A significance value of 0.008 <0.05 is obtained. So it can be concluded that there is a direct significant influence of Perceived Workplace Support on Work Life Balance, and Analysis of the influence of Work Life Balance on Employee Performance. A significance value of 0.458> 0.05 is obtained. So it can be concluded that there is no direct significant influence of Work Life Balance on Employee Performance.